Edukasi Pemasaran Kreatif Bagi UMKM Kaos Bengkulu Berdasarkan Praktik Usaha Omah Oblong Yogyakarta - Avrilina Nur Fadhillah; Tera Andini Wulansari; Vanisa Ramadhani; Monda Monda; Veny Puspita (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
The low adoption of modern marketing strategies and the lack of cultural-based product differentiation are the main constraints facing the development of garment and souvenir t-shirt MSMEs in Bengkulu City. This community service activity aimed to educate and improve the capacity of t-shirt MSMEs in Bengkulu by implementing creative marketing strategies and storytelling. The target partner was the